2003
DOI: 10.1515/cclm.2003.082
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein Lipase Gene Polymorphisms in Croatian Patients with Coronary Artery Disease

Abstract: Modifications in lipoprotein lipase levels lead to elevated triglycerides and reduced high density lipoprotein (HDL), both of which are risk factors for coronary artery disease (CAD). Hence, we examined the influence of the -93T/G, D9N, N291S, and S447X polymorphisms in the lipoprotein lipase (LPL) gene on CAD risk and lipid levels in Croatian patients with and without angiographically confirmed CAD. The N291S polymorphism was significantly associated with CAD (OR = 0.36; 95% CI = 0.13, 0.99; p = 0.048). This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Of the 21 included publications, nine provided separate associations in different populations (7,8,11,14,16,18,21,24,26). These associations were considered as separate studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 21 included publications, nine provided separate associations in different populations (7,8,11,14,16,18,21,24,26). These associations were considered as separate studies.…”
Section: Resultsmentioning
confidence: 99%
“…Based on 13 studies published up to 1997 (27), Asn291Ser heterozygous carriers had an average increase in plasma TG of 31% and an average decrease in HDL-C of 0.12 mM (P , 0.001). However, since then, a number of other studies have been published in which no association was observed (10,18,20,21,24). In addition to study power and other methodological issues, interactions with important dyslipidemic risk factors such as increasing age and weight gain could have resulted in heterogeneous findings.…”
mentioning
confidence: 99%
“…Several studies found a similar association, 8,42 -44 while others did not find an association between LPL Asn291Ser and TG levels. 45,46 Carriers of LPL Asn291Ser are found to have modest decreases of LPL activity and higher TG levels. 47 In the present study, data on LPL activity were available.…”
Section: Polymorphisms Associated With Triglyceride Levelsmentioning
confidence: 95%
“…However, Hallman et al (10) did not find any association between the HindIII(-) allele and higher LPL activity. The associations of certain polymorphic loci in the LPL promoter, introns or exons with lipid disorders and coronary artery disease (CAD) have been reported by some groups (rs285, rs1800590, rs320, rs268, rs1801177) (6)(7)(8)(11)(12)(13)(14) but contested by other authors (15)(16)(17). To the best of our knowledge, no data on the screening of such specific polymorphisms in the Saudi population have been reported.…”
Section: Introductionmentioning
confidence: 99%